2011
DOI: 10.4244/eijv6i9a192
|View full text |Cite
|
Sign up to set email alerts
|

USage of chitosan for Femoral (USF) haemostasis after percutaneous procedures: a comparative open label study

Abstract: The HemCon(r) pad significantly decreased time-to-haemostasis compared to the regular pad. The total incidence of haematoma tended to be lower in the HemCon(r) pad compared to the regular pad group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…The safety of chitosan-based hemostasis pads has been shown in previous studies. [11, 27] In this study, the frequency of allergic reactions was low, and no patients developed severe allergic reactions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The safety of chitosan-based hemostasis pads has been shown in previous studies. [11, 27] In this study, the frequency of allergic reactions was low, and no patients developed severe allergic reactions.…”
Section: Discussionmentioning
confidence: 64%
“…Compression devices (CD) or hemostasis pads are popular methods for bleeding control after radial artery punctures. [1113] In this study, we hypothesized that the combination of CD and chitosan-based pads would improve the hemostasis efficacy compared with CD alone after transradial coronary angiography or interventions.…”
Section: Introductionmentioning
confidence: 99%
“…15Y19 Previous studies have shown the hemostatic efficacy of chitosan after transfemoral percutaneous procedures. 20 In this study, the chitosan pad significantly decreased time to hemostasis compared with the TR Band. There were no major access site bleeding complications and no significant differences in the rate of minor access Abbreviations: CAO, chronic radial artery occlusion (defined as radial artery occlusion observed 30 days after the procedure); CD, compression device; CS, chitosan-based pad; EAO, early radial artery occlusion (defined as radial artery occlusion observed at 24 hours after the procedure); NS, not significant.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, there are difference heparin dose, ACT, and duration for manual compression. Recently, there are some reports for HemComTM pad for hemostasis after cathetel [9,10], however there are no precious guideline for compression time for using HemComTM pad. In our study, blood pressure and sheath sizes had not affected hemostasis duration.…”
Section: Control Hemcommentioning
confidence: 99%